Loob as Relational Interiority: A Contribution to the Philosophy of the Human Person - Alejo, Albert E., SJ (Archīum Ateneo, 2018)
This paper is a meditation on the Filipino philosophical concept of ‘loob.’ Literally, loob means ‘inside’ or ‘interior,’ but within the horizon of the Tagalog language and the culture that has nourished my interior conversation, my social relation, and my ecological conversion, loob has meant so much more than a circumscribed space, or a container of discursive baggage, or an object for academic project. As the paper reveals, loob has an inner structure that consists of the abot-malay (ambit of consciousness), the abot-dama (ambit of feeling), and the abot-kaya (ambit of strength). From its literal image to its spatial metaphor of a relational interiority, loob opens up a whole anthropological and moral discourse of pagpapakatao (being and becoming human) that promises to enrich our growing literature on alternative philosophical discourse.